Divulgar o Brasil civilizado. O uso da imprensa e a divulgação da literatura como meios de remodelar a imagem do Brasil na França (1883-1901) - Tanize Costa (Les Cahiers de Framespa)
Fighting against the stereotype of « exotic Brazil », present in the French press of the late 19th century, Brazilian propagandists – among whom Count de Barral and José de Santa-Anna Nery – tried to establish an image of their country as modern and civilized. The use of the press is one of the main strategies used. Through it, they informed about Brazilian history, current events, and culture. The dissemination of Brazilian literature was, in this context, an essential mean through which they tried to shape a positive image of Brazil in France. Through analyses of Revue du Monde Latin, this article demonstrates the practices used by these mediators to deconstruct the images of Brazil considered as erroneous, spread by the French press in the late 19th century.